Growth and Reproductive Performance of Yankasa Ewes Fed Varying Levels of Dietary Premix - S. M Ramalan; T. Z Adama; I. C Alemede; D. N Tsado; J. O Alabi; J. O Alagbe (Journal La Lifesci, 2022)
The purpose of this research was to assess the influence of nutritional premix on the growth and reproductive performance of confined Yankasa ewes. The experiment was designed using a Complete Randomized Design (CRD), in which twenty-five (25) Yankasa lambs were randomly assigned to five (5) treatment groups, each with five animals. The animals were randomly assigned to groups based on their weights and given baseline diets and four amounts of premix produced industrially and locally. Throughout the duration, 1 kilogram of basal feed (5 percent of the ewe's body weight) was supplied daily. Dietary premix was fed to the animals at four inclusion levels (0.25, 0.50, 0.75, and 1) in the morning in a restricted area; the amount of feed supplied and left over was recorded daily. The sheep were weighed at the start of the trial and then regularly afterwards. The study's results indicated that dietary interventions had an influence on final weight, total weight increase, and feed conversion ratio (P0.05). However, the dietary treatments had no significant effect on average daily weight increase, total feed intake, or average daily feed intake (P>0.05). Additionally, the findings indicated that when the amount of premix added to the diet rises, the final and total weight gain increases. The findings of T5 vary considerably from those of T1 and T2, but are statistically equivalent to those of T3 and T4. However, animals fed T5 (14.86) exhibited a higher feed conversion ratio (P0.05) than those fed T2 or T1.